2022
DOI: 10.1007/s11240-021-02210-3
|View full text |Cite
|
Sign up to set email alerts
|

CO2 supplementation eliminates sugar-rich media requirement for plant propagation using a simple inexpensive temporary immersion photobioreactor

Abstract: In vitro plant propagation systems such as temporary immersion bioreactors (TIBs) are valuable tools that enable production of disease-free plants with improved traits. However, TIB systems can be expensive, difficult to implement, and prone to contamination due to sugar rich propagation media. Using rapidly growing chicory root cultures to expedite design-build-test cycles, we report here an improved, low-cost version of a previously reported Hydrostatically-driven TIB (Hy-TIB) that facilitates economical use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Subsequent monthly subculture of whiteflies on 2-week-old cabbage provided hundreds of whiteflies to screen other plant species for their effectiveness as a maintenance host plant (MHP). Maceration of axenic whiteflies onto permissive microbial growth media confirmed the absence of culturable microorganisms, including the absence of slow-growing plant endosymbionts 24 . In screening alternative axenic plant hosts, three different assessments were made: (1) ease of PTC for given tissue culture vessel, (2) the effectiveness of the host for whitefly maintenance based on easily recoverable whitefly for transfer, and (3) observations of whitefly life cycle indicating feeding, egg lay and nymph development to adult (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Subsequent monthly subculture of whiteflies on 2-week-old cabbage provided hundreds of whiteflies to screen other plant species for their effectiveness as a maintenance host plant (MHP). Maceration of axenic whiteflies onto permissive microbial growth media confirmed the absence of culturable microorganisms, including the absence of slow-growing plant endosymbionts 24 . In screening alternative axenic plant hosts, three different assessments were made: (1) ease of PTC for given tissue culture vessel, (2) the effectiveness of the host for whitefly maintenance based on easily recoverable whitefly for transfer, and (3) observations of whitefly life cycle indicating feeding, egg lay and nymph development to adult (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Beauregard and meristem maintenance procedure 54 Routine Plant Tissue Culture: PTC and an axenic whitefly colony were maintained in a standard laboratory room designed to provide roughly 25 o C with large numbers of plant culture growth racks with a 16:8 diurnal light cycle, PAR levels of roughly 110 μmoles m -2 s -1 , and the GA7's roughly 6 inches from light. Dioscorea Yam Basic Medium (YBM) as described previously 24 . Subculturing was ideally executed monthly but could be delayed to up to 6 months if GA7 tissue culture vessels were sealed with strips of plastic wrap to prevent water loss.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, excellent growth and involvement of propagules can be achieved by enriching the percentage of CO 2 and light intensity in culture vessels (Aragon et al, 2005;Aragon et al, 2010;Curtis and Tuerk, 2008). Trauger et al (2022) also showed how CO 2 enrichment affected the growth of cocoa somatic embryos and yam nodal cultures. According to their findings, increased CO 2 during plant propagation considerably enhanced the development of cocoa and yam propagules and eliminated the requirement for added sugars in the tissue culture growth medium.…”
Section: Temporary Immersion Bioreactorsmentioning
confidence: 92%
“…Furthermore, excellent growth and involvement of propagules can be achieved by enriching the percentage of CO 2 and light intensity in culture vessels ( Aragon et al., 2005 ; Aragon et al., 2010 ; Curtis and Tuerk, 2008 ). Trauger et al. (2022) also showed how CO 2 enrichment affected the growth of cocoa somatic embryos and yam nodal cultures.…”
Section: Bioreactor Systems For Plant Propagationmentioning
confidence: 96%
“…Subsequent monthly subculture of white ies on 2-week-old cabbage provided hundreds of white ies over the next month to screen other plant species for their effectiveness as a maintenance host plant (MHP). Maceration of axenic white ies onto permissive microbial growth media con rmed the absence of culturable microorganisms, including the absence of slow-growing plant endosymbionts (Trauger et al 2022). In screening alternative axenic plant hosts, three different assessments were made: (1) ease of PTC for given tissue culture vessel, (2) the effectiveness of the host for white y maintenance based on easily recoverable white y for transfer, and (3) observations of white y life cycle indicating feeding, egg lay and nymph development to adult (Fig.…”
Section: S2-b Additional File 1))mentioning
confidence: 96%